2004
DOI: 10.1063/1.1622351
|View full text |Cite
|
Sign up to set email alerts
|

Predicting thermal displacements in modular tool systems

Abstract: In the last decade, there has been an increasing interest in compensating thermally induced errors to improve the manufacturing accuracy of modular tool systems. These modular tool systems are interfaces between spindle and workpiece and consist of several complicatedly formed parts. Their thermal behavior is dominated by nonlinearities, delay and hysteresis effects even in tools with simpler geometry and it is difficult to describe it theoretically. Due to the dominant nonlinear nature of this behavior the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The maximal correlation and optimal transformation approach were applied recently to nonlinear dynamic systems to identify delay in lasers [35] and partial differential equations in fluid dynamics [37]. The ACE algorithm turned out to be a very efficient tool for nonlinear data analysis [16,35,39,43,44]. …”
Section: Model-based Data Analysismentioning
confidence: 99%
“…The maximal correlation and optimal transformation approach were applied recently to nonlinear dynamic systems to identify delay in lasers [35] and partial differential equations in fluid dynamics [37]. The ACE algorithm turned out to be a very efficient tool for nonlinear data analysis [16,35,39,43,44]. …”
Section: Model-based Data Analysismentioning
confidence: 99%
“…These approaches on the one hand aim at modeling one or more regulation processes, and on the other hand provide model parameters which should be used to answer clinically relevant questions. In this tutorial we have introduced an approach which is very promising in data-driven modeling and modelbased data analysis [Wessel et al, 2000b;Wessel et al, 2004a;Wessel et al, 2004b;Wessel et al, 2006]. We have found that the maximal correlation method is a powerful tool for medical data analyses and for solving mechanical engineering problems.…”
Section: Discussionmentioning
confidence: 99%
“…This makes the result less sensitive to the data distribution. The maximal correlation and optimal transformation approach have recently been applied to nonlinear dynamical systems especially to model river flow data [Chen & Tsay, 1993], to identify delay in lasers [Voss & Kurths, 1997] and partial differential equations in fluid dynamics , to predict thermal displacements in modular tool systems [Wessel et al, 2004a;Wessel et al, 2004b] and to medical data analyses [Wessel et al, 2000b;Wessel et al, 2006]. A more general review on nonlinear system identification is given in .…”
Section: Nonlinear Model Based Data Analysismentioning
confidence: 99%